Carbon Paste Electrode Modified with Two Layers Poly(glutamate) for Amperometric Determination of Ascorbic Acid - Muhammad, Andrizki
Ascorbic acid (AA) is one of the chemical compounds which is necessary for growing and improving of human body tissues. Therefore, it is very important to consume appropriate amount of ascorbic acid because our own body cannot produce AA. In this research, an amperommetric technique using modified carbon paste electrode (CPE) for determination of ascorbic acid has been developed. Because oxidation process of AA on the surface of carbon paste electrode is slow, modification of CPE was needed in order to improve the kinetic of AA oxidation. The modified electrode was fabricated through an electropolymerization of glutamic acid onto the carbon paste electrode using cyclic voltammetry technique. The carbon paste electrode was modified with two layers of poly(glutamic acid). The first layer attached to the surface of CPE was non imprinted poly(glitamic acid) (NIP) and the second layer was molecularly imprinted poly(glutamic acid) (MIP) layer attached to the NIP surface. This electrode (CPE-NIPMIP) was characterized using ammperometric technique with constant potential of 391 mV vs Ag/AgCl. The calibration curve was linear in the contretation range of 10 µM – 100 µM with detection limit of 2.2 µM. Determination of AA in real sample showed very accurate results and in agreement those with spectrophotometry method (? = 511 nm) also obtains a good result.